Body adiposity indices are associated with hypertension in a black, urban Free State community - Ronette Lategan; Violet L. van den Berg; Corinna M. Walsh (AOSIS, 2014)
Background: Non-communicable diseases, including hypertension, are increasing rapidly in resource-poor, developing countries amongst populations transitioning from traditional to westernised lifestyles; and are associated with excess weight. Aim: To investigate the relationship between hypertension and various indices of body adiposity in a transitioning, urban, black population. Setting: Three hundred and thirty-nine adults (25-64 years) from a larger cross-sectional study (Assuring Health for All in the Free State) conducted in Mangaung, South Africa, were included. Methods: Standard techniques were used to determine blood pressure, HIV status, body mass index (BMI), waist-to-height ratio (WHtR) and body adiposity index (BAI). Results: Approximately 40% of the sample was HIV-positive and 63.4% hypertensive, with the greatest risk of hypertension being amongst older men. Based on BMI, 23.0% were overweight and 32.1% obese. Waist-to-height ratio showed that 58.6% had increased cardiovascular risk. Mean BAI was 34.1%, whilst 76.3% had a body fat percentage in the overweight/obese category. Waist circumference representing increased cardiovascular risk was found in 44.3% of women and 3.9% of men. Significant positive correlations between mean arterial bloodpressure and BMI (r = 0.261; p < 0.001), WHtR (r = 0.357; p < 0.001) and BAI (r = 0.245; p <0.001) were found. WHtR was a stronger predictor of mean arterial pressure than BMI or BAI. HIV status showed an inverse correlation with all adiposity indices (p < 0.001). Conclusion: Our findings promote WHtR as a practical screening tool for increased hypertension risk in populations undergoing westernisation, and support weight loss as afirst-line intervention for the prevention and management of hypertension.